The Indonesian Crisis: End of a Regime - Ley-López, Sergio (Revista Mexicana de Política Exterior, 2022)
The author gives a detailed, chronological analysis of events prior to outbreak of the crisis in Indonesia as a point of departure for considering the possible future scenarios. The article studies the crisis that occurred in this country in 1997, not just from the macroeconomic perspective, but also from a political and social viewpoint. Ley López reviews the adjustments the Indonesian government made to avoid a crisis like the one that had already exploded in Thailand; the agreements Suharto’s government signed with the IMF; the aid from countries like Malaysia and Singapore in restoring confidence in the Indonesian economy; the credibility crisis in the banking system; inflation, and devaluation of the rupee. He also examines the social and political events such as the student demonstrations, Suharto’s resignation, Habibie’s ascent to power, along with the process of political and economic reforms the government has implemented. Lastly, the author forecasts that, given the size of the political-social and economic crisis, Indonesia’s recovery will be a long, painful process.